Pengaruh Dukungan Keluarga Terhadap QOL Pasien Skizofrenia: Systematic Review - Tsanifiandi, Fauzi; Fitryasari, Rizki; Iskandar, Iskandar; Astuti, Trihaningsih Puji; Hidayati, Nurul (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2024)
ABSTRACT Introduction: Patients with schizophrenia experience symptoms that affect their quality of life such as working, socializing, and other daily activities. Families have the main task of caring for patients when they are sick. This systematic review aims to investigate QoL in schizophrenia patients who receive family support during the treatment process. Methods: Springer Link, Pubmed, Sage Journal, and Science Direct databases were used for literature search. The literature used was published within the last 5 years that examined family support on QoL of patients with schizophrenia. Articles were read and analyzed using the PRISMA procedure to guide this review. Results: The literature search yielded 375 research articles, 11 of which were included after multiple selections in the systematic review. Overall, patients with schizophrenia when supported by their families had significantly higher QoL. Family support influenced QoL on the constructs of social interaction, psychological status and functional ability in patients with schizophrenia. Conclusion: Further research is needed on the development of interventions that utilize family support through family empowerment in its implementation.application of this therapy. Future CBT programs can focus on developing the content of CBT by utilizing the internal and external factors of adolescents based on the findings of this study. Key words: family support, quality of life, schizophrenia